The Wives’ Healing Process in the Aftermath of Infidelity - Ginanjar, Adriana Soekandar (Makara Human Behavior Studies in Asia, 2009)
The purpose of this research is to find an in-depth and holistic understanding of the betrayed wives’ healing process. Also studied is any supporting factors that helps them in their healing process. This study uses qualitative method with case study design. Participants are researcher’s clients, which consist of three wives whose husbands are involved in extra marital affairs. They have been in therapy for at least six months or undergo at least ten continuous therapy sessions. This research uses several data collection methods, as data triangulation, to improve the credibility of the research. The main data source is the researcher’s notes taken in the therapy sessions. In addition, the researcher also conducts additional in-depth interview to inquire the participants’ healing process in details, and the supporting factors that help them grow in a positive direction. Another source of data is observation through the therapy process. The result shows that husbands’ infidelity causes an extremely negative impact on the well-beings of their wives. They simultaneously undergo many intense negative feelings and this condition is usually extremely hard for them to experience. Every individuals go through their unique healing process, but in general they all go through the following stages: 1) shock and disbelief, 2) experience and coping with intense negative emotions, 3) talking about marital problem with the husbands, 4) repairing the damage. Healing process is influenced by internal and external factors. The factors that are significant in healing process are: religion, emotional supports, personality characteristics, positive changes of the husbands, self-actualizing activities, and therapy process.